Um lugar: muitas histórias o processo de formação de professores de Matemática na primeira instituição de ensino superior da região de Montes Claros/ norte de Minas Gerais (1960-1990) - Shirley Patricia Nogueira de Castro e Almeida (2015)
The research reported in this thesis aimed to investigate the process of mathematics teachers education in the first higher education institution in the region of Montes Claros, northern Minas Gerais, in the 1960-1990 period. The choice of the period is due to the creation in 1968 of the first course of Mathematics of the region, and the transformation in 1990 of the private institution that originally housed it in the state authority, later renamed State University of Montes Claros (UNIMONTES). In addition to written materials, sixteen narratives from teachers involved in the course as founders, teachers or students were used, according to the oral history methodology. The research is part of the project of mapping the training and work of Mathematics teachers in Brazil, developed by the Group Oral History and Mathematics Education (GHOEM). The analysis of interviews and several other sources showed that the movement of creating the institution and the Mathematics course was constituted of a complex and multifaceted process, influenced by political, economic and educational issues of the national and local scenery. As occurred in other Brazilian institutions, the training of mathematics teachers in the course in the investigated period was an emergency action, based on demands from educational legislation, political and economic interests. During the investigated period (1960-1990) we found several aspects of permanence and continuity, such as emphasis on the study of mathematical disciplines content; the supporting presence of educational disciplines; the theoretical rigor proclaimed as essential to the course of Mathematics; the remarkable idea that the teacher must be certified and qualified to act effectively in teaching. We also verified that there were some ruptures related to the perspective of the education of mathematics teachers. Teachers who studied at that time told us that they made a conscious choice for teaching, and they succeeded in that function. However, those of these teachers who are still teaching have told us that they have noticed that very few students are interested in teaching.